Case Report: Insulin-Dependent Diabetes Mellitus and Diabetic Keto-Acidosis in a Child With COVID-19 - Nielsen-Saines, Karin; Li, Erica; Olivera, Adriana Martinez; Martin-Blais, Rachel; Bulut, Yonca (Frontiers in Pediatrics, 2021)
During the COVID pandemic, a surge in pediatric T1DM cases is occurring, more likely due to the presence of autoantibody-induced immune dysregulation triggered by COVID-19. We describe one such case in a previously healthy 7-year-old with asymptomatic COVID-19 presenting with a high nasopharyngeal SARS CoV-2 virus load, detectable COVID-19 IgG antibodies, diabetic keto-acidosis and islet cell autoantibodies. COVID-19 is not a trivial disease in children and adolescents and can lead to lifelong sequelae such as T1DM. Raising awareness about the potential association between COVID-19 and T1DM in youth is critical.